Examining the Impact of Teachers’ Professional Development on the Quality of Implementing School Self-evaluation Policy: A Case study in Dubai - Hossni, Mohamed (2020)
School self-evaluation policy is meant to effectively enhance schools’ performance and to evaluate education transparently. However, the implementation process of this policy faces many caveats. To attain its benefits, practitioners should be well-informed about the procedures of implementing the school self-evaluation policy. To this end, teachers’ professional development sets the foundation to the school self-evaluation policy implementation and builds organisational capacity for evidence-based practice. Accordingly, this study aims to investigate the impact of teachers’ professional development on the quality of implementing school self-evaluation policy. Hence, the study sets three objectives. The first objective is to determine teachers’ and administrations’ awareness about school self-evaluation and professional development. The second objective is to identify the impact of professional development on school culture. The third objective is to evaluate the impact of teachers training and professional development on the quality of implementing school self-evaluation policy. To achieve this, the study utilised the mixed methods case study design. The sample of the study was two administrators, four heads of departments, and 34 teachers. The study developed four instruments: a questionnaire, interviews, focus group discussion, and content analysis. Considering the study limitations, findings of the study indicated that the effective teachers’ professional development reflect school’s needs. Moreover, it revealed the importance of teachers’ professional development on the implementation of school self-evaluation policy. Based on this, the study proposed set of recommendations to be consider for policymakers and policy implementers. These recommendations highlight three areas of focus: designing effective professional development, building the capacity of educational institutions to conduct self-evaluation, and considering transparency and impartiality in the implementation of self-evaluation.